SISTEM INFORMASI PENYUSUTAN AKTIVA TETAP SEBAGAI PENGELOLAAN ASET TETAP DENGAN METODE GARIS LURUS BERBASIS MULTIUSER - Luvianti Anggreini; Dendy Kurniawan (CV. Denasya Smart Publisher, 2024)
In a company, assets are one of the most important working capital that needs to be managed well. This includes maximizing the value of its benefits as well as its existence so that it can be used optimally and the need for accurate recording of assets so that they can be used for good decision making. One type of asset/asset in a company is fixed assets/assets. Fixed assets/assets are one of the items on the balance sheet besides current assets/assets, long-term investments, reserve funds, and other assets/assets. PT. Thanks to Sejati Transindo (BESTINDO) Semarang as one of the document and goods delivery service companies, so far it still uses Ms. Excel for recording, calculating and reporting company fixed assets. Some of the weaknesses of this old system are: 1) the asset/asset management system is still simple, 2) fixed asset/asset data is not yet integrated and does not have a database, 3) there are inconsistencies and calculation errors, 4) the recording and reporting system is still takes quite a long time to process, 5) incomplete data will have an impact on inappropriate decision making, and 6) the absence of an integrated Accounting Information System (AIS) means that the management of fixed assets/assets in the company cannot be carried out properly because the data The condition, condition and value of the company's fixed assets/assets have not been recorded properly and accurately. This research designs an AIS for calculating and reporting depreciation of fixed assets using the straight line depreciation method using Visual Basic 6.0 and MySQL. The objectives of this research are: 1) to help calculate depreciation of fixed assets/assets owned by the company, 2) to provide information about the detailed condition of each asset/fixed asset owned by the company so as to help the company in managing fixed assets/assets, and 3) to help present precise and accurate reports for the purposes of the company's internal financial reports and taxation.